2004
DOI: 10.1002/ts.158
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient deficiency symptoms in yams (Dioscorea spp.)

Abstract: Symptoms of nutritional deficiencies in D. alata and D. rotundata were observed when yam plants were grown in nutrient solutions from which any of the following had been omitted: N, P, K, Ca, Mg, Zn, Fe, B, Mn, Cu and Mo. The symptoms of deficiency of major elements were visible on plants of both species. The omission of Fe, B and Mo produced characteristic symptoms on the leaves of D. rotundata, but D. alata showed symptoms only in response to Fe deficiency. The omission of minor elements led to poor growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
3
7
0
Order By: Relevance
“…At 15 to 60 mg l -1 leaves of TDa 95/00361 contained high levels of Fe and TDr 89/02565 leaves had high levels at 40 to 60 mg l -1 Fe. The levels of N, P, K, Ca, Mg, Zn, Mn and Cu in the leaves of D. alata and D. rotundata were similar to those reported by Shiwachi et al (2004). Fe accumulation in the leaves was higher in D. alata and lower in D. rotundata leaves than in previous report when Fe was applied at high concentration (Shiwachi et al 2004).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…At 15 to 60 mg l -1 leaves of TDa 95/00361 contained high levels of Fe and TDr 89/02565 leaves had high levels at 40 to 60 mg l -1 Fe. The levels of N, P, K, Ca, Mg, Zn, Mn and Cu in the leaves of D. alata and D. rotundata were similar to those reported by Shiwachi et al (2004). Fe accumulation in the leaves was higher in D. alata and lower in D. rotundata leaves than in previous report when Fe was applied at high concentration (Shiwachi et al 2004).…”
Section: Resultssupporting
confidence: 85%
“…The solution with a full complement of nutrients, 0.81 g l -1 KNO 3 , 0.94 g l -1 Ca(NO 3 ) 2 .4H 2 O, 0.49 g l -1 MgSO 4 .7H 2 O, 0.21 g l -1 NaH 2 PO 4 .2H 2 O, 3 mg l -1 H 3 BO 3 , 0.22 mg l -1 ZnSO 4 .7H 2 O, 2 mg l -1 MnSO 4 .4H 2 O, 0.05 mg l -1 CuSO 4 .5H 2 O, 0.02 mg l -1 Na 2 MoO 4 .2H 2 O and 15.1 mg l -1 Fe-EDTA (3 mg l -1 of Fe) used for water culture in yams (Shiwachi et al 2004) served as the control. It had pH 6.5 and EC 2.2 mmho.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Positive correlation was observed between tuber yield and leaf concentrations of N, P, K, and Mg. This reaffirmed the importance of these nutrients in yam as stated in other studies (Obigbesan, 1981;Shiwachi et al, 2004).…”
Section: Downloaded By [Mcmaster University] At 12:33 05 February 2015supporting
confidence: 90%
“…While leaf K concentration ranged from 2.52-3.25% in TDr '97/00609', it was 1.61-1.85% in TDr '93-32' even at 600 kg ha −1 NPK application. The range of leaf Zn concentration observed in the present study was within the range reported by Shiwachi et al (2004) when yam varieties were grown in nutrient solution. However, lower ranges were observed for Ca and Mg in our study.…”
Section: Discussionsupporting
confidence: 78%